THER-01. Precision brain tumor therapy by AAV-mediated oncogene editing. (3rd June 2022) - von Soosten, Laura; Haar, Janina; Frehtman, Veronika; Holderbach, Stefan; Belzen, Julius Upmeier zu; Jendrusch, Michael; Okonechnikov, Konstantin; Pfister, Stefan M; Grimm, Dirk; Leuchs, Barbara; Jones, David; Kutscher, Lena M; et al.
Abstract: Pediatric high-grade glioma is a heterogeneous group of highly malignant tumors of the central nervous system, with a median overall survival of less than two years after diagnosis, demanding novel treatment options. One innovative approach is gene therapy, which has so far been hampered for cancer treatment owing to the lack of a system targeting tumor cells specifically. To overcome this limitation, we established a novel strategy for gene therapy, combining tumor cell-specific adeno-associated virus (AAV) variants with oncogene-specific CRISPR-Cas nucleases. We screened 177 different Cas9/gRNA combinations targeting the genes encoding H3 K27M or BRAF V600E, and identified highly specific nucleases that edited the oncogenic allele but left the respective WT loci intact, which we validated by PCR amplicon sequencing. Next, we intravenously injected an AAV library engineered to encode its own capsid DNA into mice harboring patient-derived xenograft tumors driven by H3 K27M or BRAF V600E . After 21 days, we resected neoplasms and separated mCherry-labeled tumor cells from normal surrounding cells by fluorescence-activated cell sorting. Using the DNA from tumor cells as template, we generated a second AAV library, which was utilized in another round of in vivo selection. At the end of each screen, DNA from tumor cells, surrounding cells, and control tissues (liver and spleen) was analyzed by amplicon sequencing. Strikingly, we identified multiple AAV variants that were highly and recurrently enriched in the analyzed tumor tissues. We are currently validating these variants by intravenously injecting selected, GFP-encoding AAVs to tumor-bearing mice and by subsequently analyzing their distribution throughout the aforementioned tissues. We will combine oncogene-specific nucleases with these validated AAV variants and analyze their anti-tumoral efficacy in a preclinical setting. Furthermore, we plan to adapt this approach to allografted mice, evaluating its feasibility and efficacy in syngeneic models.